A historical-developmental study of classical Indian philosophy of morals - Prasad, Rajendra, 1926-; Centre for Studies in Civilizations (Delhi, India); Project of History of Indian Science, Philosophy, and Culture (New Delhi : Concept Pub. Co. : Project of History of Indian Science, Philosophy and Culture, Centre for Studies in Civilizations, 1964)
Contributed articles.
Includes index.
Includes bibliographical references.
Keywords: Ethics -- India -- History; Philosophy, Indic; Hindu philosophy; Religion and ethics; Ethics in literature; Vedic literature -- History and criticism